The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1958
DOI: 10.1021/j150562a018
|View full text |Cite
|
Sign up to set email alerts
|

A Thermodynamic Study of Some Complexes of Metal Ions with Polyamines

Abstract: The value of An at 27°is a measure of the amount of decomposition product still gaseous at room temperature. The fact that An at 27°is still large, in many cases, indicates that at least some of the decomposition products are of low molecular weight. The nature of the volatile decomposition products for certain of these compounds is currently being investigated. The results of this study will be reported in a later paper.The nature of the solid residues obtained from the decomposition of the acetylacetonates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1968
1968
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…In the water exchange study, two different exchange rates were observed, leading the authors to propose a cis-octahedral arrangement for the Ni(tren)(H20)~ + species. Other authors have suggested tetrahedral (Bertsch, Fernelius & Block, 1958) or trigonal bipyramidal (Jonassen & Thilemann, 1963). In this paper, we present solid-state structural results for the compound bis (triaminoethylamine)(triethylenetetramine)dinickel(II) perchlorate, C~sHs4NI2Ni4+.4C10~ (I), supporting the concept of a cis-octahedral arrangement.…”
Section: -2701/87/081494-0450150supporting
confidence: 76%
“…In the water exchange study, two different exchange rates were observed, leading the authors to propose a cis-octahedral arrangement for the Ni(tren)(H20)~ + species. Other authors have suggested tetrahedral (Bertsch, Fernelius & Block, 1958) or trigonal bipyramidal (Jonassen & Thilemann, 1963). In this paper, we present solid-state structural results for the compound bis (triaminoethylamine)(triethylenetetramine)dinickel(II) perchlorate, C~sHs4NI2Ni4+.4C10~ (I), supporting the concept of a cis-octahedral arrangement.…”
Section: -2701/87/081494-0450150supporting
confidence: 76%
“…The structure of synthesized compound contains a novel example of hexafurcated (acceptor) hydrogen bonds and accompanying three-dimensional channel assembly. We note that measurements of the complexation enthalpies and entropies for cis-and trans-1,2-diaminocyclohexane with Ni(II) as well as with other divalent metals have been reported [183].…”
Section: Issuementioning
confidence: 84%
“…The complexes of Cu(l1) and Ni(1I) with 1,3-propanediamine are much less stable than those with 1,2-ethanediamine. The -AH values for binding are larger with propanediamine, in keeping with its stronger basicity, but the stabilities are dominated by the more favorable entropy change when the 5-membered ring is formed (29). Loss of freedom of the ligand is so great with 7-membered ring formation that 1,4-butanediamine (putrescine) does not form Cu(II), Ni(II), or Zn(I1) complexes in aqueous solution (29), although these complexes can be isolated from absolute alcohol (30).…”
mentioning
confidence: 97%
“…The -AH values for binding are larger with propanediamine, in keeping with its stronger basicity, but the stabilities are dominated by the more favorable entropy change when the 5-membered ring is formed (29). Loss of freedom of the ligand is so great with 7-membered ring formation that 1,4-butanediamine (putrescine) does not form Cu(II), Ni(II), or Zn(I1) complexes in aqueous solution (29), although these complexes can be isolated from absolute alcohol (30). It has been estimated (24) that diamine-Cu(l1) chelate rings of 5, 6, and 7 members add respectively 5.3-7.0, 4.6-6.1, and 2.0-3.0 to the log K , value for complex formation.…”
mentioning
confidence: 97%
See 1 more Smart Citation